2014
DOI: 10.1111/1365-2745.12292
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of herbivores slows down recovery after experimental warming and nutrient addition in an alpine plant community

Abstract: Summary 1.Global change, such as climate warming and nitrogen deposition, has been predicted to induce non-reversible regime shifts in natural ecosystems. However, we lack knowledge of the potential for recovery from global change perturbations and factors influencing the recovery rate. 2. We examined the recovery of an alpine plant community from a combined warming and nutrient addition experiment, which initially caused profound changes in plant community composition and diversity. We also examined whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 64 publications
2
26
0
Order By: Relevance
“…Despite this, the number of experimental environmental change studies on bryophytes and lichens is small. While numerous studies have investigated vascular plants in these severe environments, there are few that have resolution at species level or community responses that include bryophyte and lichen diversity (Bjerke et al, 2011;Klanderud, 2008;Lang et al, 2012;Olsen and Klanderud, 2014;Potter et al, 1995). Bryophytes and lichens are frequently used as ecological indicator species (Cristofolini et al, 2014;Mölder et al, 2015), but in experimental environmental change studies bryophytes and lichens are not usually identified at species level Hill and Henry, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the number of experimental environmental change studies on bryophytes and lichens is small. While numerous studies have investigated vascular plants in these severe environments, there are few that have resolution at species level or community responses that include bryophyte and lichen diversity (Bjerke et al, 2011;Klanderud, 2008;Lang et al, 2012;Olsen and Klanderud, 2014;Potter et al, 1995). Bryophytes and lichens are frequently used as ecological indicator species (Cristofolini et al, 2014;Mölder et al, 2015), but in experimental environmental change studies bryophytes and lichens are not usually identified at species level Hill and Henry, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Contrastingly, for Collembola and Oribatida species composition, we found differences in community composition between treatments and controls to persist nine years after cessation of the treatments. Although mammalian herbivory did influence community composition of both Collembola and Oribatida, it did not promote trajectories toward the original community composition as was found for the vegetation (Olsen and Klanderud ). Hemi‐edaphic Collembola that live near the soil–surface interface, in particular F. quadrioculata , were most responsive to environmental treatments and remained dominant in Collembola communities nine years after treatments were discontinued.…”
Section: Discussionmentioning
confidence: 61%
“…We propose several mechanisms that can explain why Collembola abundances returned to pre‐treatment levels, even though treatments are still visible in the vegetation composition (Olsen and Klanderud ; K. Klanderud, S. L. Olsen, and R. E. Roos, personal observation ). First, nutrient addition may have had a direct, stimulatory effect on the microbial and fungal community, which is an important part of the micro‐arthropod diet (Mack et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Increased nutrient availability in the soil, either through artificial fertilization or increased decomposition, will change the species composition. In particular, the cover and frequency of lichen and bryophyte species are reduced, while graminoids and some deciduous shrubs are generally favored (Klanderud 2008, Olsen & Klanderud 2014. This change in species composition most often results in reduced biodiversity.…”
Section: Changes In Plant Distributionmentioning
confidence: 99%